2006
DOI: 10.1103/physrevlett.97.036805
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Spin Relaxation in Submicron InGaAs Wires

Abstract: We investigate electron-spin dynamics in narrow two-dimensional n-InGaAs channels as a function of the channel width. The spin relaxation times increase with decreasing channel width, in accordance with recent theoretical predictions based on the dimensionally constrained D'yakonov-Perel' mechanism. Surprisingly, the suppression of the relaxation rate, which is anticipated for the one-dimensional limit, is observed for widths that are an order of magnitude larger than the electron mean free path. We find the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
133
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 21 publications
10
133
2
Order By: Relevance
“…Motivated by a recent experiment 3 we studied spin relaxation in narrow wires with spin-orbit coupling. To this end we have solved the Eilenberger equation and the spin diffusion equation in the presence of spin-orbit interaction 15 supplemented by boundary conditions for both charge and spin degrees of freedom assuming translational invariance along the wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by a recent experiment 3 we studied spin relaxation in narrow wires with spin-orbit coupling. To this end we have solved the Eilenberger equation and the spin diffusion equation in the presence of spin-orbit interaction 15 supplemented by boundary conditions for both charge and spin degrees of freedom assuming translational invariance along the wire.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has been motivated by a recent experiment, where the size dependence of the spin relaxation time of an n-InGaAs wire has been measured via Faraday rotation spectroscopy. 3 The size dependence sets in when the wire width is of the order of several bulk spin relaxation lengths. The observed behavior is nonmonotonic with an initial increase followed by a sharp decrease at the smallest wire widths.…”
Section: Introductionmentioning
confidence: 99%
“…This anisotropy, which arises due to the interplay between the Rashba and Dresselhaus SO coupling strengths, could be estimated comparing the spin relaxation time for two distinct channel orientations. Finally, our model could also be used to study the anisotropy of the spin relaxation time [35] and its dependence on the width of the wire [36][37][38][39][40][41], even in the limit of a few-subband quantum wire when the semiclassical approximation is no longer valid.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Mal'shukov et al pointed out, other mechanisms can limit the eventual suppression of the spin relaxation, e.g., the BIA induces a component of the D'yakonov-Perel' spin relaxation which is independent of the channel width [20]. We would like to note that in a first experimental study, an effective slowing of the Dyakonov Perel spin relaxation mechanism has been observed in conducting channels of n-InGaAs quantum wires [22,44]. The results are consistent with a dimensionally-constrained D'yakonov-Perel' mechanism.…”
mentioning
confidence: 99%
“…As a precursor of the one-dimensional limit, long spin relaxation times are expected when the channel width w is smaller than the electronic mean free path l e (w < l e ). As a result, spin relaxation mechanisms, which are intrinsic to the two-dimensional electron systems (2DES), can be suppressed very efficiently [22].…”
mentioning
confidence: 99%